Navigating security and human rights: the Malaysian Maritime Enforcement Agency’s response to the Rohingya refugee crisis - Aizat Khairi; Tjoetra, Afrizal; Da-Oh, Phaison (Penerbit UKM, 2025)
This article explores the dilemma faced by the Malaysian Maritime Enforcement Agency (MMEA) as it navigates the challenging terrain of balancing human rights considerations with national security imperatives in response to the Rohingya refugee crisis. The agency’s response is marked by the delicate tension between upholding human rights obligations and addressing security concerns. This study employs a qualitative methodology, utilizing purposive sampling to identify MMEA personnel experienced in managing the Rohingya refugee crisis. In-depth interviews were conducted with respondents, employing semi-structured questions. The data collected was analyzed by content analysis and theoretical application. The ethical and legal challenges faced by the MMEA in handling the Rohingya refugee crisis are examined, considering Malaysia’s non-ratification of the 1951 Refugee Convention and its ramifications on the treatment and protection of Rohingya refugees. The securitization of migration and the perception of refugees as potential security threats further complicate the agency’s decision-making process. The MMEA endeavors to adopt a comprehensive and multidimensional approach that reconciles human rights values with security imperatives. This research underscores the imperative for enhanced regional cooperation, policy coherence, and the development of sustainable solutions. It emphasizes the protection of Rohingya refugees while concurrently addressing the legitimate security concerns of host countries, thereby framing the discussion within the broader contexts of security and human rights. The article also provides insight into how security agencies can navigate the tension between safeguarding national interests and upholding fundamental human rights values.